Readiness for Radiological and Nuclear Events among Emergency Medical Personnel - Dallas, Cham E.; Klein, Kelly R.; Lehman, Thomas; Kodama, Takamitsu; Harris, Curtis Andrew; Swienton, Raymond E. (Frontiers in Public Health, 2017)
Background Amongst medical providers, even though radiological and nuclear events are recognized as credible threats, there is a lack of knowledge and fear about the medical consequences among medical personnel that could significantly affect the treatment of patients injured and/or contaminated in such scenarios. The results of the only two nuclear detonations in war so far and more recent nuclear reactor accidents have demonstrated the remarkably inefficient response of the medical community. This study was conducted to evaluate the relative knowledge, willingness to respond, and familiarity with nuclear/radiological contamination risks among U.S. and Asian emergency medical personnel. Methods An IRB approved anonymous paper survey was distributed at various medical and disaster conferences and medicine courses in Japan and the U.S. The Surveys were written in Japanese and English and collected 4 categories of information: generalized demographics, willingness to manage, knowledge of disaster systems, and contamination risks. Results A total of 416 surveys were completed and collected. Demographics showed that physicians and prehospital responders were the prevalent survey responders. The majority of responders, despite self professed disaster training, were still very uncomfortable with and unaware how to respond to a radiological/nuclear event. Conclusion Despite familiarity with disasters both through courses and actual events, there is a paucity of comfort and knowledge regarding nuclear and radiological events amongst the medical community. Further education including course development in multiple languages promoted in multiple venues needs to occur to better educate and prepare the medical community for inevitable upcoming radiological/nuclear events.